An update on canine ehrlichiosis - MYLONAKIS (Μ.Ε. ΜΥΛΩΝΑΚΗΣ), M. E.; BILLINIS (Χ. ΜΠΙΛΛΙΝΗΣ), C.; KOUTINAS (Α. Φ. ΚΟΥΤΙΝΑΣ), A. F. (Journal of the Hellenic Veterinary Medical Society, 2018)
Canine ehrlichiosis is a common disease caused by several Ehrlichia species, such as E. canis, E. chaffeensis, E. risticii, E. ewingii, E. equi, E. platys, and an as yet unnamed granulocytotropic species or strain. Ehrlichia are tick-borne gram-negative bacteria that reside in the cytoplasm of various blood cells. The infected dogs, may manifest a wide spectrum of clinical signs, of which anorexia, depression, loss of body weight, peripheral lymphadenopathy, pale mucous membranes and bleeding tendency are the most common. The most consistent clinicopathologic findings are anemia, thrombocytopenia, leucopenia, hyperglobulinemia, and proteinuria. Apart from the clinical and clinicopathologic findings, diagnosis should be based on buffy coat, lymph node or bone marrow cytology, serology (ELISA, IFA) and/or the polymerase chain reaction (PCR). Doxycycline with or without imidocarb dipropionate constitute the mainstay of the etiological treatment, while blood transfusions, anabolic steroids, glucocorticosteroids, iron supplements and bactericidal antibiotics may be of some benefit in a certain number of cases. Effective tick control is of imperative importance for the prevention of the infection.